Mobile ID in physical access control applications - Simonetti, José Eduardo (2016)
Today there exist a myriad of different types of physical access control systems (PACS) that use a smart card or mobile device as a key. The mobile device enabled smart locks, as they are often referred to, operate using either Wi-Fi or Bluetooth. This thesis has explored the use of a third emerging wireless technology called Near Field Communication (NFC) available in mobile devices such as smartphones. Near Field Communication (NFC) technology is a relatively new technology that is on the rise and is included in almost every new mobile device. By leveraging Near Field Communication (NFC) enabled mobile devices, a highly secure access control system can be achieved and developed taking advantage of the computational power of smartphones in comparison to traditional methods the business implications are huge, Several different authentication and encryption protocols, mobile operating systems and Near Field Communication (NFC) modes of operation where analyzed and evaluated. After considerations technical considerations the Secure Remote Password authentication protocol on top of Near Field Communication (NFC) card emulation (CE) scheme with the client application running on smartphones operating system (OS) was selected. This thesis shows that Near Field Communication (NFC) enables a mobile device to act as a key in a secure access control system (PACS) and as the user base for NFC grows larger so will the likelihood that we will come to see more of these types of systems in business and organizations.